Mammalian Genomics - Ruvinsky, A (CABI, 2014)
Hardly any other area of science has experienced such dramatic development as genomics during the last 15–20 years. While genomics of many pro- and eukaryotic species progressed rapidly, mammalian genomics, despite the obvious complexity, was in the centre of development. Over the last several years, the Human Genome Project abandoned its initial academic status and became a human endeavour comparable with the flight to the moon and other extraordinary human achievements. Data from other mammalian genomes such as mouse and rat have been published recently; others for dog, cattle, chimpanzee and several more will soon follow. Incredible and unprecedented opportunities for the comparative analysis of genomes brought by these huge international efforts have already started to yield new results, and will certainly do much more in the near future. This explosion of genomic research has led to a quite widely expressed view that the genomic era is behind us, and we are entering a post-genomic era. Although terminology and attempts to categorize scientific development are usually subjective, it seems obvious to the editors of this book that the genomic era is far from being over, and there are extraordinary opportunities to expand this very productive way of generating deep understanding of the essential core of life. This vision is reflected in the structure of the book, which is composed of five linked sections. The first section is devoted to the structure of the mammalian genome and covers topics central to genomics projects. It contains four chapters, covering linkage maps, cytogenetic and physical maps, and the molecular anatomy of the human genome. The second section describes functional aspects of genomics, topics often called functional genomics. There are five chapters in this section covering different ‘omes’ including transcriptome, proteome, epigenome, regulation of genome activity and genetic networks, as well as the analysis of gene functions by genome manipulation. These fields of research provide essential information on the physiological output of the genome.